La comunicación corporal en las elaboraciones identitarias-subjetivas (2008)
ABSTRACT: The following article is a revaluation of the importance of non-verbal communication and the use of the body in studies of identity constructs. Emphasis is placed on youth and the subaltern groups, revising theoretical debates on identity, communication and the body. These debates are discussed in the context of an ethnographic study on colombias groups in the city of Monterrey, México.